Storytelling as Students' Speaking Skill Enhancement Technique - Masyita - Nurfadillah (IAIN KENDARI, 2020)
ABSTRACT In frame of mixed method research, the researcher intended to find the significant difference that occur in class XI IPA1 MAN 1 Konawe students. Through this research, the aim was to describe the main problem, how to solve it and what the improvements in speaking that are seen in students. Data is collected using observation, interview and students’ test. The test used pre-test in the first meeting and post-test in last meeting. To find the preliminary data through observation, researcher need six students from 23 students of class XI IPA 1 MAN 1 Konawe. To analyze the data, this study uses test normality to gain the result from Paired sample test (t-test) formula. The result that is calculated from SPSS V.26 shows that tcount is bigger than t-table (13.122 > 1.717). The calculation proves the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It means that there was significant improvement in students’ speaking skill after using Storytelling in their English class of XI IPA 1 MAN 1 Konawe. This study implies that students really need not just material but also technique which can facilitate them in understanding the subject and mastering it. Keyword: Normality test, Paired sample test, Speaking skill, Storytelling